El “pragmatismo principista” de la política exterior de México en los votos sobre Cuba en la OEA (1962-1964) - Velázquez Flores, Rafael (El Colegio de México A.C., 2021)
The central aim of this paper is to explain the reasons why the government of Adolfo López Mateos (alm) produced three different votes at three different meetings of the Organization of American States (oas), over a relatively brief period, on issues relating to Cuba and the anti-communist policy of the United States. To do this it analyzes the concept of the win-sets of Robert Putnam’s two-level game theory, the decision-making process of Mexico’s foreign policy towards Cuba in the context of these three meetings. The different votes are explained on the basis of the size of the win-sets in each case, which were determined on the basis of different internal and external circumstances that are presented in each moment. The decision depended principally on the interest of the government and the impact of the pressure groups, both internal and external, that had an interest in the issue at the time and in the prevailing domestic and international situation. The essay seeks to demonstrate the following hypothesis. In Mexican public opinion, there is a widespread view that the government of alm supported Cuba at these meetings of the oas. However, the aim here is to show that in fact, Mexico was aligned with the interests of the United States and not with those of the Castro regime.